PERSONAL DATA PROTECTION ON INTERNATIONAL DIGITAL TRADE: HARMONIZING STATE REGULATIONS THROUGH A COMMON STANDARD - Gea, Gita Venolita Valentina; Wijaya, Jill Grezelda; Clarissa, Olivia; Witanto, Aurelia Kimberley Clarance (Faculty of Law, Parahyangan Catholic University, 2025)
The advancement of digital trade has brought considerable benefits, yet it also presents significant challenges, particularly in protecting users’ personal data. Digital trade platforms commonly require users to share personal information, raising concerns over data security and accountability. Current regulations governing personal data protection are primarily limited to national or regional legal systems, resulting in a lack of harmonization that impedes the seamless flow of international trade. This paper explores the pressing need for a standardized global framework for personal data protection within the digital trade landscape. Using a normative juridical approach, the study examines various regional legal regimes and assesses the relevance of international trade principles in addressing data protection issues. The analysis highlights the absence of a globally recognized standard for personal data protection in digital trade and finds that existing international instruments are inadequate for meeting current challenges. Given UNCITRAL’s role in shaping international trade law, the development of a new legal framework, such as a Model Law, should be pursued. As a form of soft law, a Model Law offers a practical and adaptable tool for harmonizing legal standards across jurisdictions. Its adoption would enhance legal certainty and ensure the protection of personal data in international digital trade transactions, thereby upholding the rights of all parties involved.